007: SACROILIAC JOINT VACUUM PHENOMENON AMONG PATIENTS WHO UNDERWENT LUMBAR AND ABDOMINOPELVIC CT-SCANS IN A TERTIARY PRIVATE HOSPITAL. A STUDY ON PREVALENCE AND REPORTING RATES. (24th August 2015) - Tabora, Leiza Joy Saguid
Abstract : Background: Sacroiliac joint vacuum phenomenon (SJVP) is a common incidental finding but its presence is often not included in the official CT scan reports. It is uncommonly foundin the literature, and there is lack of data on its prevalence and clinical significance. Determination of SJVP can possibly be used as an indicator in predicting the development or presence of certain diseases and conditions such as infection, degenerative sacroiliac joint diseases, osteonecrosis and other arthropathies. Objectives: The objectives of this studyare to determine the prevalence of sacroiliac joint vacuum phenomenon among adult patients who underwent lumbar and abdominopelvic CT scan in a tertiary private hospital for a period of one year and to determine how many patients diagnosed with SJVP were correctly identified based on the official CT scan results. Methods: Multiplanar abdominopelvic and lumbar CT images from January 1, 2013 to December 31, 2013 were retrospectively reviewed for the presence of linear gas density in the sacroiliac joints, known as sacroiliac joint vacuum phenomenon. This included 1355 subjects, (709 males and 646 females) excluding patients less than 20 years old, who seldom undergo CT scan because of the known effects of ionizing radiation. The prevalence of SJVP was determined. Review of electronic records whether this was mentioned in the CT scan reports by board-certified radiologists was done. Result: Of 1355 patients, 743 have sacroiliac joint vacuum phenomenon. There is a higher prevalence of SJVP in females, 61% and in patients belonging to ≥60 years old age group, 43%. Among 743 patients with SJVP, only 4 (0.5%) were reported in the official CT results. Conclusion: SJVP is a prevalent finding and has higher rates in women and in the elderly. The phenomenon is an underreported finding in CT scan examination reports signed out by different board-certified radiologists.